A study of estimated blood loss during maxillary sinus radical operation - YOSHIKAWA, Takatoshi; NISHIMURA, Koichi; SANO, Kimito; KATO, Joji; KANRI, Tomio; MATAGA, Izumi (Japanese Journal of Oral and Maxillofacial Surgery, 1989)
We have examined the estimated blood loss of 200 patients had a maxillary sinus radical operation in the central operating room of The Nippon Dental University, School of Dentistry at Niigata Dental Hospital from February 1979 to May 1987. The subjects included 106 males and 94 females, ranged from class 1 to class 2, according to ASA classification. Their ages ranged from 1. 5 to 73 years and the average age was 42.1±12.6 years. Their body weights ranged from 7.9 to 92.8kg and the average body weight was 56.4±10.0kg. Referring to the methods of anesthesia, nitrous oxide-oxygen-halothane was applied to 94 cases, nitrous oxide-oxygen-enflurane to 60 cases, and neurolept anesthesia to 46 cases, 181 cases in which vasoconstrictors were used during operation. A correlationship was observed between body weight and estimated blood loss. The estimted blood loss would increase with an increase in the operative time, a correlationship was observed between these factors. Cases of odontogenic maxillary sinusitis had larger estimated blood loss than those of postoperative maxillary cyst, with a statistically significant difference observed. There were no statistically significant differences observed in relation to methods of anesthesia, kinds of vasoconstrictors used, and whether or not a vasoconstrictor was used. The least estimated blood loss was shown by the group having an average systolic blood pressure (SBP) of 100 mmHg or lower, resulting in statistically significant differences from the respective groups having 101 to 120 mmHg and 121 mmHg or higher.